2009
DOI: 10.1111/j.1365-2141.2009.07664.x
|View full text |Cite
|
Sign up to set email alerts
|

Mild increases in serum hepcidin and interleukin‐6 concentrations impair iron incorporation in haemoglobin during an experimental human malaria infection

Abstract: Summary The correct selection of individuals who will benefit from iron supplements in malaria‐endemic regions requires improved insight in the effects of malaria on host iron homeostasis and innovative biomarkers. We assessed sequential changes in serum hepcidin and in traditional biochemical iron status indicators during an experimental Plasmodium falciparum malaria infection with five adult volunteers. The haemoglobin content of reticulocytes (Ret‐He) and of mature red blood cells (RBC‐He) represented iron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 33 publications
3
67
0
Order By: Relevance
“…However, correlation analysis of our data reveals an inverse relationship between the levels of iron and hepcidin expression. This observation is consistent with a recent study of de Mast and colleagues (34). The results from these authors have indicated that an increase in serum hepcidin levels is associated with a decline in serum iron concentrations in human volunteers infected with P. falciparum.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, correlation analysis of our data reveals an inverse relationship between the levels of iron and hepcidin expression. This observation is consistent with a recent study of de Mast and colleagues (34). The results from these authors have indicated that an increase in serum hepcidin levels is associated with a decline in serum iron concentrations in human volunteers infected with P. falciparum.…”
Section: Discussionsupporting
confidence: 83%
“…Upregulation of hepcidin expression has been observed in livers of mice infected with pathogenic bacteria (8,9). Recent studies have indicated that urinary or serum hepcidin levels are increased in patients with malaria (18)(19)(20)34). However, little is known about the regulation of hepatic hepcidin expression during malaria infection.…”
Section: Discussionmentioning
confidence: 96%
“…We recently showed in an experimental human malaria model that even a mild increase in serum hepcidin, to concentrations in the range of those observed in the current study, induces hypoferremia and a steep fall in the hemoglobin content of reticulocytes, which is suggestive of impaired iron incorporation in hemoglobin. 12 Moreover, the lower values of hemoglobin, mean corpuscular volume, serum iron concentration and transferrin saturation in children with asymptomatic parasitemia also support the presence of functional iron deficiency. Since asymptomatic P. falciparum and P. vivax parasitemia are chronic and relapsing conditions, a possible delocalization of iron with iron retention in monocytes/ macrophages may theoretically increase the risk of anemia and of infections with intracellular bacteria (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Previously, our group studied hepcidin expression in anemic Tanzanian children with febrile P. falciparum malaria with high parasite densities and in malaria-naïve Dutch volunteers who were experimentally infected with P. falciparum. 11,12 Hepcidin concentrations were increased in both groups and associated with profound disturbances in iron homeostasis, suggesting that iron supplements should be withheld during symptomatic P. falciparum malaria. To our knowledge, no data are yet available on the effects of asymptomatic P. falciparum or P. vivax parasitemia on hepcidin expression.…”
Section: Introductionmentioning
confidence: 99%
“…The difference between Ret-Hgb and RBC-Hgb, expressed as ⌬Hgb, provides information on the current iron availability and short-term iron incorporation for erythropoiesis owing to the long life span of mature erythrocytes compared to reticulocytes (3). As a consequence, in the presence of absolute iron deficiency, iron supplementation is expected to substantially raise the Ret-Hgb and ⌬Hgb within several days (4-6), while no effect, or only limited effect, is expected in the pure functional iron deficiency of the inflammatory state (patients with ACD).…”
Section: Replymentioning
confidence: 99%